DAMPAK EKSPOR BUAH MANGGIS INDONESIA KE VIETNAM TERHADAP INDONESIA TAHUN 2011-2014 - Friansisco Danestio; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The research analyzesthe impact of Indonesian mangosteen fruit exports to Vietnam on Indonesia. One of the export commodities that now dominate the horticultural export market from Indonesia to Vietnam is the mangosteen fruit.Mangosteen fruit is oneof Indonesiafeatured product. With the trade cooperation between the twothis country then the mangosteen fruit of Indonesia must compete with other exporters. With Indonesia natural resources, Indonesia is able to compete with exportersThe research teoritically has been built by using Liberalism perspective. The kind of this research is qualitative research. The data is based on secunder data through literature study such as book,website, and each other.The final result of this research is that Indonesia can increase the export value of mangosteen fruit to Vietnam. Indonesian mangosteen fruit exports have increased significantly, Mangosteen fruit becomes one of the mainstay in Indonesian horticultural export commodities. Mangosteen fruit has the largest amount of export in horticultural export commodities. Various efforts were made by the Indonesian government to increase the export power of horticulture so as to be able to compete in the domestic market to the international market. The government efforts are producing good results because every year the export of Indonesian mangosteen fruit to the country of Vietnam has increased. Although the export volume is not as high as in other countries but exports to Vietnam have increase.Keywords : Mangosteen, Impact of exports